First Observations of Magnetosonic Waves With Nonlinear Harmonics. Issue 6 (3rd June 2020) - Huang, S. Y.; Deng, D.; Yuan, Z. G.; Jiang, K.; Li, J. X.; Deng, X. H.; Yu, X. D.; He, L. H.; Wei, Y. Y.; Xu, S. B.
Abstract: Magnetosonic waves, with the frequency between proton cyclotron frequency and lower hybrid frequency, mainly occur near the Earth's magnetic equatorial plane and play an important role in the magnetospheric dynamics. In this paper, we report unusual magnetosonic waves with nonlinear harmonics observed by Magnetospheric Multiscale mission in the magnetotail. These magnetosonic waves have multiband enhanced electromagnetic power spectral densities ( B w / B 0 up to 1/45) with the frequency from below to above the lower hybrid frequency and are quasi‐perpendicular propagating and linearly polarized. The frequency of the fundamental band is much higher than the proton cyclotron frequency f ci (i.e., 35 f ci ). We identified these emissions as high‐frequency magnetosonic waves with nonlinear harmonics. These are the first observations of such high‐frequency magnetosonic waves with the frequencies of harmonics higher than the lower hybrid frequency in the Earth's magnetosphere to the best of our knowledge. Given the absence of ring distributions for the protons and the easy coupling between compressed mode and its electromagnetic term, we propose that these nonlinear harmonic structures of the observed magnetosonic waves are likely generated by the nonlinear wave‐wave coupling among electromagnetic terms of the fundamental and higher harmonic waves. Key Points: First observations of high‐frequency multiharmonic magnetosonic waves with the frequencies of harmonics higher than the lower hybrid frequency are observed in the Earth's magnetosphere Such magnetosonic waves have nonlinear harmonics Nonlinear harmonics are likely to be generated by nonlinear wave‐wave coupling interaction